Implementasi Hadist Tasamuh Dalam Meningkatkan Moderasi Beragama - Darsul,; Rahman, Arif; Tasbih, (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2022)
This study aims to investigate the implementation of tasamuh hadith in Maradekaya Village. This type of research is qualitative which is presented descriptively. The research took place from April to September 2021. The primary data sources in this study were religious leaders, religious instructors, and the community, both Muslim and non-Muslim. Secondary data include books, magazines, newspapers, television, radio, and other relevant written works—methods of collecting data through observation and interviews. The research instruments used were cameras, voice recorders, pens, and notebooks. Data analysis was carried out by means of data condensation, data presentation, data triangulation, and drawing conclusions. The results show that even though people do not understand and have not memorized the tasamuh hadith, it can be concluded that the tasamuh hadiths have been implemented well in Maradekaya Village, Makassar City because people understand each other between religious adherents, give each other the right and freedom to worship according to their beliefs. each. Also, live side by side safely and peacefully. The implication of this research is that many terms related to Islamic fiqh are not yet known in the community, such as tasamuh. There has also been no massive movement to promote the hadith about tasamuh. It is recommended that hadith as a second legal basis must be adequately socialized, not primarily in social relations only in universities but also in the general public.